Clariant reports 7% increase in sales for the first quarter of 2018. Issue 6 (June 2018) - Unknown
Abstract : For the first three months of 2018, Switzerland's Clariant reported net sales of CHF1.722 billion (c. €1.49 billion), an increase of 7% in both Swiss francs and local currency terms compared to CHF1.602 billion in 1Q 2017. EBITDA before exceptional items also improved by 7% in Swiss francs, up from CHF250 million to CHF268 million, while the corresponding EBITDA margin before exceptional items remained stable at 15.6%.